Microbial Cell Factory of Baccatin III Preparation in Escherichia coli by Increasing DBAT Thermostability and in vivo Acetyl-CoA Supply - Huang, Jia-jun; Wei, Tao; Ye, Zhi-wei; Zheng, Qian-wang; Jiang, Bing-hua; Han, Wen-feng; Ye, An-qi; Han, Pei-yun; Guo, Li-qiong; Lin, Jun-fang (Frontiers in Microbiology, 2022)
Given the rapid development of genome mining in this decade, the substrate channel of paclitaxel might be identified in the near future. A robust microbial cell factory with gene dbat, encoding a key rate-limiting enzyme 10-deacylbaccatin Ⅲ-10-O-transferase (DBAT) in paclitaxel biosynthesis to synthesize the precursor baccatin Ⅲ, will lay out a promising foundation for paclitaxel de novo synthesis. Here, we integrated gene dbat into the wild-type E. coli BW25113 to construct strain BWD01. Yet, it was relatively unstable in baccatin Ⅲ synthesis. Mutant gene dbatS189V with improved thermostability was screened out from a semi-rational mutation library of DBAT. When it was over-expressed in an engineered strain N05 with improved acetyl-CoA generation, combined with carbon source optimization of fermentation engineering, the production level of baccatin Ⅲ was significantly increased. Using this combination, integrated strain N05S01 with mutant dbatS189V achieved a 10.50-fold increase in baccatin Ⅲ production compared with original strain BWD01. Our findings suggest that the combination of protein engineering and metabolic engineering will become a promising strategy for paclitaxel production.